Gender, Literature and Identity: A Practice Perspective of Humanism - Calderón-Rojas, Ericka (2016)
In this paper the methodology used in the course Gender, literature and identity, by Centre for General Studies, headed awareness of gender issues in the university student body is exposed; gender understood as a branch of feminism theory that seeks to eradicate the social segregation of minorities, both men and women, and its historical importance for the defense of human rights. Based on this, the design of an interactive project group, which is periodically worked and supervised way between staff team member and facilitator academic course are encouraged. Once the project completed, the results and experiences are presented, most successful and important for personal and professional growth of its participants. Among the many highlights works presented photographic exhibitions, videos about sexist language, a theatrical performance and activities of literature written by women for primary and secondary education.